Introduction - Mary Gobbi (Tuning Journal for Higher Education)
Three of the eight papers that comprise this Edition of the Journal, focus on different aspects of intergenerational learning. The remaining five papers address internationalisation strategies in Africa; career paths of local and international doctoral students; peer tutoring programmes, perspectives of science teachers, including mathematics and physics, and models of Higher Education. The papers reflect a varied range of participant countries both in terms of the authors, but perhaps more importantly the study sites including several from Latin America (Africa, Chile, Bulgaria, Paraguay, Peru, Spain, Turkey and Uzbekistan). Similarly, the programmes of study range from dental education, geological sciences, teacher education (in various forms), ongoing development of academic staff and the evolution of embryonic Higher Education systems. From these rich and diverse papers, one can see the crucial importance of eliciting, at national level, (1) those factors that are unique to the national context and culture; and (2) those that are like other systems and countries, whether in a historical moment of evolution, or those that resonate with contemporary and parallel contexts. Building the national and international evidence base in Higher Education requires both types of study, if only to satisfy the criterion of generalisablity.